Hereditary Essential Tremor - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Twenty index patients with hereditary essential tremor, and 93 first degree and 38 more distant relatives were studied at the Institute of Neurology, Queen Square, London, and Oldchurch Hospital, Romford, UK.